Al-Sihah Dictionary: Between Features and Constructive Criticism for its Study and Application in the Contemporary Era - Sabiila, Diyanah Hanin; Taufiq, Mirwan Akhmad (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The development of the Arabic lexicon has increased because more people are studying the Arabic language. A lexicon or dictionary is essential in learning foreign languages ​​to help people define new vocabulary and understand the meaning of certain words. Every dictionary written by an author is certainly not free from errors. This study aims to criticize the Arabic dictionary entitled as-shihah. The researcher analyzed it using the descriptive approach in analyzing the dictionary. The advantages of this dictionary include: First, it is concerned with including all the correct words of the Arabs and limited to them. Second, according to qaafiyah (rhyme), its method helps people compose poetry. Third, Al-Jawhari refers to some unknown, reprehensible, ugly, or abandoned words in the language. Fourth, he mentioned some Arabized and coined words. Fifth, there were many morphology, grammar, or central derivation issues. Among the negatives of the correct dictionary are The most critical errors of this dictionary are the misprints and distortions, Al-Jawhari’s mistake in arranging the materials in an internal order, and he began the material with the name of the passive participle and not the beginning of the verb or the infinitive.